2008
DOI: 10.1130/g25032a.1
|View full text |Cite
|
Sign up to set email alerts
|

Model for tectonically driven incision of the younger than 6 Ma Grand Canyon

Abstract: Accurate models for the incision of the Grand Canyon must include characterization of tectonic infl uences on incision dynamics such as active faulting and mantle to surface fl uid interconnections. These young tectonic features support other geologic data that indicate that the Grand Canyon has been carved in the past 6 Ma. New U-Pb dates on speleothems are reinterpreted here in terms of improved geologic constraints and understanding of the modern aquifer. The combined data suggest that Grand Canyon incision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
169
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(186 citation statements)
references
References 8 publications
(20 reference statements)
13
169
0
Order By: Relevance
“…1 ISTerre Université de Grenoble 1, CNRS-IRD, F-38041 Grenoble, France. perturbation to oceanic circulation [Poore and White, 2011], large scale continental drainage reorganizations [Shephard et al, 2010] or the formation of major geomorphic features such as the Grand Canyon [Karlstrom et al, 2008].…”
Section: Introductionmentioning
confidence: 99%
“…1 ISTerre Université de Grenoble 1, CNRS-IRD, F-38041 Grenoble, France. perturbation to oceanic circulation [Poore and White, 2011], large scale continental drainage reorganizations [Shephard et al, 2010] or the formation of major geomorphic features such as the Grand Canyon [Karlstrom et al, 2008].…”
Section: Introductionmentioning
confidence: 99%
“…Adding to this the expectation that every late Quaternary lava dam emplaced since ca. 850 ka would trigger its own transient knick, a migrating knickzone model seems far more likely than does the steady incision model of Karlstrom et al (2008) and Crow et al (2014) to explain the long-term incision history of Grand Canyon.…”
Section: Knickzone Height and Incision Rate Are Both "Unreasonable"mentioning
confidence: 97%
“…Even broad wavelength, mantle-induced surface uplift could trigger a transient knick. Karlstrom et al (2008) and Crow et al (2014) inferred a temporally steady Grand Canyon incision rate and argued that that steady rate suggests mantle-driven surface uplift is responsible for incision. But Whipple and Tucker (1999) demonstrated that a spatially broad change in elevation such as this would trigger migration of a transient knickpoint prior to establishment of steady-state incision.…”
Section: Knickzone Height and Incision Rate Are Both "Unreasonable"mentioning
confidence: 99%
“…North plateaus underwent a series of uplift processes, the most recent estimate of elevation increase is more than 2 km, which we believe to be relative to thermal expansion associated with lithospheric thinning and magmatic-related crustal thickening [3]. Karlstrom et al [5] suggested a static framework for incision of the Grand Canyon which envisions a previously elevated Colorado Plateau that was passively incised by a deepening canyon system (and progressive watertable lowering) in response to base-level fall. However, based on analyses of modern mantle velocity structure beneath the region and the geoid, Sine et al [6] and Karlstrom et al [5] provide compelling evidence for a more dynamic framework involving mantle dynamics due to small-scale asthenospheric convection beneath the western edge of the Colorado Plateau.…”
Section: Introductionmentioning
confidence: 97%